2008
DOI: 10.1529/biophysj.107.117796
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Modulation of Kv4:KChIP-1 Channels by External K+

Abstract: In response to a prolonged membrane depolarization, inactivation autoregulates the activity of voltage-gated ion channels. Slow inactivation involving a localized constriction of the selectivity filter (P/C-type mechanism) is prevalent in many voltage-gated K(+) channels of the Kv1 subfamily. However, the generalization of this mechanism to other Kv channel subfamilies has remained uncertain and controversial. In agreement with a "foot-in-the-door" mechanism and the presence of ion-ion interactions in the pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 57 publications
3
64
0
Order By: Relevance
“…It has been reported that deletion of the Kv4 N terminus, which induces fast inactivation presumably by pore occlusion, results in slower inactivation (30,34). Sequestering the proximal N terminus of Kv4, KChIPs also gives to rise to slow inactivation of the channel (27,42). All of these findings suggest that inactivation of Kv4 channels is also likely to be mediated by other mechanisms such as closed-state inactivation (43).…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that deletion of the Kv4 N terminus, which induces fast inactivation presumably by pore occlusion, results in slower inactivation (30,34). Sequestering the proximal N terminus of Kv4, KChIPs also gives to rise to slow inactivation of the channel (27,42). All of these findings suggest that inactivation of Kv4 channels is also likely to be mediated by other mechanisms such as closed-state inactivation (43).…”
Section: Discussionmentioning
confidence: 96%
“…IChMASCOT was used as previously described [35][36][37] to obtain the best global fit of a Markov kinetic model to DRG nociceptor Kv3.4 currents. The global fit involves the simultaneous fitting of multiple voltage and time dependent current properties.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…[1][2][3] Unlike other much more well-studied potassium channels, such as Shaker [4][5][6] and KcsA, In a recent issue of Channels we presented results 14 on the K v 4.3 partial N-terminal deletion mutant D2-39 (which removes amino acids 2-39 of the proximal N-terminal domain). In contrast to predictions of popular K v 4 gating models, 2,[9][10][11][12] our D2-39 analysis 14 yielded several unexpected results, among which the following two were possibly the most surprising: i) partial N-terminal deletion not only removed the prominent rapid component of macroscopic inactivation, but also slowed the net rate of recovery from inactivation; and ii) coexpression of KChiP 2b (K Channel interacting Protein 2b) 1,3,15 while having no major effect on the rate of D2-39 macroscopic inactivation, produced significant acceleration of the rate of D2-39 recovery. The first result (which is generally consistent with previous K v 4…”
mentioning
confidence: 77%
“…1, inset). Beginning at an interpulse interval of Dt = 60 msec (so as to "bypass" this initial complication of sigmoidicity 14 ), the constrained exponential best fit to the mean D2-39 + KChIP 2d data points resulted in an estimated recovery time constant (trec = 120 msec) that was very similar to that of D2-39 + KChiP studies 2,[9][10][11][12] indicates that deletion of the K v 4.3 proximal N-terminal, while mimicking the slowing effect of KChIP 2b on macroscopic inactivation, [15][16][17] does not mimic the acceleratory effects of KChIP 2b on recovery. The second result (which is in contrast to previous K v 4.2 studies 2,10,11 ) indicates that an intact N-terminal proximal domain is not obligatory for KChIP2 isoforms to exert acceleratory effects upon K v 4 channel recovery.…”
mentioning
confidence: 99%